Non-linear behaviour of one-bay steel frames with semi-rigid connections - Lim, Pui Yan (2007)
This project studies the static non-linear behaviour of plane steel frames with semi-rigid connections. To describe the non-linear behaviour of the semi-rigid connections, the three-parameter power M-fr model is used. ANSYS software package is used for the non-linear analysis of the frames. Finite element models that include geometrical, material and connection non-linearities are considered in this study. Material and geometrical non-linearities are modeled by a bilinear defined stress-strain curve and specifying large displacement for the analysis. The influence of connection fixity on the force transfer mechanism and stability behaviour of semirigid steel plane frame structural system under uniformly distributed vertical loads and lateral loads are investigated. It can be concluded from the results that the connection flexibility has significant influence on the behaviour of the frames. The connection flexibility contributes to significant increase in the point displacements and change in the distribution of internal forces in the system. The influence of the geometric non-linearity increases with the loads. The influence is higher when semirigid type of connections are used than in the case of fully rigid connections. It is also observed that the critical load carrying capacity of the system significantly decreases with the increase in the flexibility of joints.